Scenarios of selective logging on genetic diversity and basal area of Araucaria angustifolia populations, with base in Ecogene modeling - Dal Bem, Edjair Augusto [UNESP]; Messias Bittencourt, Juliana Vitoria; Teixeira de Moraes, Mario Luiz [UNESP]; Sebbenn, Alexandre Magno (Ipef-inst Pesquisas Estudos Florestais, 2015)
The Ecogene model was used to investigate how selective logging of Araucaria angustifolia trees affects the long-term basal area (BA) and genetic diversity of populations and what are the scenarios of selective logging to ensure sustainability in timber production. The study was conducted with data from microsatellite loci, demographic, ecological in a fragmented population of the species. Selective logging scenarios, representing different combinations of minimum cutting diameter (MCD), intensity of exploitation (IE) and cutting cycle (CC) were studied. For MCD of 50 cm and IE 20, 40 and 90% the AB recovered the original situation after 54, 74 and 84 years, respectively. For MCD 75 cm AB recovery occurred at 31, 44 and 56 years, respectively, and for MCD 100 cm, the recovery time was at most 22 years. The estimated genetic distance between the population in the initial and final age of simulation indicated that the scenarios with larger changes in allele frequencies were based on MCD 50 cm. This is a clear example of the impacts of selective logging on the genetic diversity of exploited populations, and that Brazilian law does not lead to sustained timber production in A. angustifolia. The simulation results show that smaller impacts of selective logging on demography, AB and genetic parameters occur with the adoption of larger MCD and lower IE.
Keywords: Conifers; sustainable forest management; species of sub-tropical trees; selective logging; simulation models